Students Anxiety on iGeneration of Post-Structuralism at SMA Kuala Kapuas and Palangka Raya - Oktaviani, Santia; Pradita, Yola; Yuel; Rudie; Munte, Alfonso (EDUJAVARE: International Journal of Educational Research, 2023)
The purpose of this research is to find out the extent to which narratives are aired, spread, staged, and raised through the three research subjects from Generation Z who are located in one of the provinces in Indonesia, namely the province of Central Kalimantan, especially from research subjects who come from three different high schools. Data searches through three different high schools display various narratives, subjective experiences as psychological experiences when dealing with turmoil, homework, and school, as well as forms of socialization that appear in students' daily lives. The research is based on qualitative research with data search through secondary sources. Secondary sources through various journals were obtained through previous research related to the topic, crossed each other, and gave distance while supporting the narratives displayed by the three research subjects from Central Kalimantan at the upper education unit level. In addition, researchers also used book sources as primary sources to support the poststructuralist presence. The results showed that although the three research subjects came from Generation Z, living in schools, homes, and other social environments, they showed different characteristics with the term characteristics attached to Generation Z. However, in the end, the researcher concluded that the characteristics of Generation Z differed from those of Generation Z. Although in the end, researchers concluded that the characteristics that are detected at the ontological level regarding Generation Z as part of the development or poststructuralist pattern, the facts on the ground speak that the place, school culture, and students become a marker that the culture itself even though it is developing, it still cannot be released even though the era shows now (when researchers conducted research) in poststructuralism as well as the presence of generation Z. The discontinuity of identity participation of the three research subjects is the continuation of the previous generations, namely the baby boomers, generation X, and Y.